Stephen Gilman, Del Arcipreste de Hita a Pedro Salinas. Universidad, Salamanca, 2002; 376 pp. - Sol Mora, Pablo (El Colegio de México, 2004)
Se reseñó el libro: Del Arcipreste de Hita a Pedro Salinas.